Cloud and convection frequencies relative to small-scale geographic features - Gibson, Harold M., author; Vonder Haar, Thomas H., author; Cooperative Institute for Research in the Atmosphere (Fort Collins, Colo.), publisher (Colorado State University. Libraries, 1990)
Visible and infrared data of GOES West were collected for nine hours each day during the summer of 1986. Cloud frequency charts were computed for the area from Mississippi east to Georgia and the Gulf of Mexico north to Tennessee for each of the nine hours as well as convection frequency charts to four convection intensities as defined by the temperature of the cloud top. Strong diurnal tendencies were noted. As was expected, these charts show that over the land areas cloudiness is at a maximum during the early afternoon hours with convection at a maximum in the late afternoon and evening. Cloudiness and convection are at a maximum during the nocturnal hours over the Gulf of Mexico. Cloud frequency shows a strong relationship to small terrain features. Small fresh water bodies have cloud minima in the afternoon hours relative to the surrounding terrain while higher terrain, especially if there is a sharp slope, have cloud maxima. The adjacent lower terrain exhibits afternoon cloud minima due to divergence caused by the valley to mountain breeze. The sea breeze-induced convergence causes relative cloud maxima over near-shore land areas with the stronger maxima over peninsulas. It is shown that the sea breeze results in convergent low level flow regardless of the weather over a peninsula or over land adjacent to a bay or inlet. Cloud frequencies tend to be larger both in magnitude and areal extent over peninsulas. Small scale geographical features show no relationship to convection, but larger peninsulas and extensive higher terrain show late afternoon convection maxima.
January 1990.
Principal investigator: Thomas H. Vonder Haar.
Keywords: Clouds -- Diurnal variations; Cloud physics; Cloud forecasting